1995
DOI: 10.1159/000120975
|View full text |Cite
|
Sign up to set email alerts
|

Delayed and Progressive Brain Injury in Children and Adolescents with Head Trauma

Abstract: We performed serial CT scans on 351 children and adolescents with serious closed-head injury. Delayed or progressive lesions were encountered in 145 (41%). The occurrence of such delayed cerebral injuries correlated with the severity of the initial head trauma, with the presence of major extracranial injury and with studies of coagulopathy on admission. The presence of delayed cerebral injury had a profound influence on survival and recovery from head trauma, especially when the initial severity of the head in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 36 publications
1
40
2
1
Order By: Relevance
“…In pediatric guidelines and retrospective pediatric studies of all traumatic brain injuries, repeat imaging is recommended for some observed patients given concern for progression of injury [8,16,24,25,26,27]. While repeat imaging was common in our study population, the initial repeat CT image showed an increase in hematoma size in a minority of patients and led to surgery in only 1 patient.…”
Section: Discussionmentioning
confidence: 92%
“…In pediatric guidelines and retrospective pediatric studies of all traumatic brain injuries, repeat imaging is recommended for some observed patients given concern for progression of injury [8,16,24,25,26,27]. While repeat imaging was common in our study population, the initial repeat CT image showed an increase in hematoma size in a minority of patients and led to surgery in only 1 patient.…”
Section: Discussionmentioning
confidence: 92%
“…These evolving lesions consist of extraaxial hematomas and intracerebral hematomas. There have also been multiple recommendations for repeat scans after the initial head CT [8,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Two pathogenetic mechanisms for secondary traumatic damage stand out among those proposed, excitotoxicity and apoptosis. 8 -35 Blocking each of these processes elicits protective effects in experimental models for brain and spinal cord trauma.…”
mentioning
confidence: 99%